Bowel management post major joint arthroplasty: results from a randomised controlled trial. Issue 2 (May 2015) - Ross-Adjie, Gail M.; Monterosso, Leanne; Bulsara, Max
Abstract Aim To evaluate the effect of a new post-operative bowel protocol in total hip and total knee replacement patients. Background Up to 65% of total hip and total knee replacement patients experience some degree of constipation post-operatively. A lack of robust evidence to guide bowel management and reduce constipation in this cohort was the impetus for this study. Design A multisite cluster randomised trial in private secondary and tertiary hospitals. Methods In total 331 patients were recruited across seven Australian hospitals over 13 months. Control participants (n = 171) received routine bowel management whilst intervention participants (n = 160) received bowel management as per the trial protocol. Results Intervention patients took 6 days less than controls to return to normal bowel function, and were more than seven times more likely to return to normal bowel function by day 5 post operatively. Age, gender and length of pre-operative fasting had no effect on these outcomes. Conclusion These results support the use of the Murdoch Bowel Protocol® for hip and knee replacement patients and may be relevant for other patient groups who experience opioid induced bowel dysfunction.